Pathways to Modern Chemical Physics - Califano, Salvatore (Springer Berlin Heidelberg : Imprint: Springer, 2012)
In this historical volume Salvatore Califano traces the developments of ideas and theories in physical and theoretical chemistry throughout the 20th century. This seldom-told narrative provides details of topics from thermodynamics to atomic structure, radioactivity and quantum chemistry. Califano's expertise as a physical chemist allows him to judge the historical developments from the point of view of modern chemistry. This detailed and unique historical narrative is fascinating for chemists working in the fields of physical chemistry and is also a useful resource for science historians who will enjoy access to material not previously dealt with in a coherent way.